The role of cynobacteria in improving photosynthesis in paddy / Ahmad Afiq Rezali - Rezali, Ahmad Afiq (Faculty of Plantation and Agrotechnology, 2017)
Improving photosynthesis by genetic engineering has been a favorable way for crop improvement as intended to improve photosynthetic yield and better water-use efficiency (WUE). One of the approaches is integrating component of the highly efficient CO2-concentrating mechanism (CCM) is that available in cyanobacteria (blue-green algae) into the C3 plant chloroplast. There are four progressive phases in engineering cyanobacteria CCM components into C3 plant. First phase (1a), is transplanting cyanobacteria bicarbonate transporters to the rice chloroplast. Using genomic expression and targeting chloroplast to increase CO2 level to provide significant improvement in performance of photosynthetic. Improvement in photosynthesis can achieve 28% by introducing both of the single gene, cyanobacteria bicarbonate transporter into rice chloroplast, known as BiCa and SbtA. First phase (1b) is more challenging integration of useful cyanobacteria carboxysome into the chloroplast by genome transformation. The other phases will be more proggressively more complex. It takes longer time to engineer other useful cyanobacteria CCM components into chloroplast and targeting C4 photosynthetic and WUE efficiencies. Other phases will be addition of NDH-1-type CO2 pumps and reduction of carbonic anhydrase and C3 Rubisco in the chloroplast stroma.